SURGICAL TACTICS IN THE TREATMENT OF CICATRICIAL STRICTURES OF THE BILE DUCTS BECAUSE OF THE IATROGENIC INJURIES AND AFTER RECONSTRUCTIVE OPERATIONS - A. Yu. Korolkov; V. M. Savrasov; M. A. Kitaeva; D. N. Popov; S. F. Bagnenko (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The aim of the study is to demonstrate the effective surgical technique in the treatment of cicatricial strictures of the bile ducts. MATERIAL AND METHODS. The authors analyzed the surgical treatment of 18 patients with iatrogenic cicatricial damages of the bile ducts. The development of cicatricial strictures of the bile ducts was diagnosed in all 18 patients with iatrogenic damages of bile ducts after previously performed reconstructive operations. RESULTS. biliodigestive anastomoses on the exchangeable transhepatic drains were applied for 17 patients; Y-anastomosis were applied for 1 patient. biliodigestive anastomoses on the exchangeable transhepatic drains were applied for 2 patients of the 17 on the second stage in 3 months after external drainage of the hepatic ducts. Repeated scarring of the bile ducts and anastomosis had not been observing for the 5 years of observation. CONCLUSION. The choice of surgical tactics in treatment of cicatricial strictures of the bile ducts depends on the type of stricture. high strictures appears more often. The effective treatment of them is biliodigestive anastomoses on exchangeable transhepatic drains.